2015
DOI: 10.1007/s10561-015-9505-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage closed sinus lift: a new surgical technique for maxillary sinus floor augmentation

Abstract: Bone tissue atrophy may constitute a relative contraindication for implantation. The methods used in reconstruction of the alveolar ridge within the lateral section of the maxilla have been well known but not perfect. Presentation of the two-stage, closed sinus lift technique as well as efficacy evaluation of reconstruction of the alveolar ridge in the maxilla within its vertical dimension with the use of this technique. The total procedure was performed in 26 out of 28 patients qualified for the study. The he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
(20 reference statements)
0
12
1
Order By: Relevance
“…The mean total bone height gain of 8.31 mm for the B-1 group is similar to a study by Winter et al [ 17 ] They found the mean bone height gain for implants (n = 58) placed with a 1-stage transalveolar sinus lift and an initial RBH of <4 mm was 9.12 mm. Mean bone height gain of 1st sinus lifting in the B-2 group was 5.43 mm, which is greater than the gain of 3.94 mm for 26 implants reported by Krasny et al; [ 11 ] however, the mean RBH in their study was 4.22 mm. There were significant differences in the bone height gain of 1st sinus lifting for the 2-stage surgery groups (B-2 and L-2) following graft healing; the mean gain in the B-2 group (5.43 mm, SD = 2.21) was significantly lower than the L-2 group (8.44 mm, SD = 2.72).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The mean total bone height gain of 8.31 mm for the B-1 group is similar to a study by Winter et al [ 17 ] They found the mean bone height gain for implants (n = 58) placed with a 1-stage transalveolar sinus lift and an initial RBH of <4 mm was 9.12 mm. Mean bone height gain of 1st sinus lifting in the B-2 group was 5.43 mm, which is greater than the gain of 3.94 mm for 26 implants reported by Krasny et al; [ 11 ] however, the mean RBH in their study was 4.22 mm. There were significant differences in the bone height gain of 1st sinus lifting for the 2-stage surgery groups (B-2 and L-2) following graft healing; the mean gain in the B-2 group (5.43 mm, SD = 2.21) was significantly lower than the L-2 group (8.44 mm, SD = 2.72).…”
Section: Discussioncontrasting
confidence: 72%
“…A transalveolar sinus lift is usually recommended when the initial residual alveolar bone height (RBH) is more than 5 mm; the lateral window sinus lift is suggested when the bone height is less than 5 mm. [ 10 ] However, Krasny et al [ 11 ] successfully reconstructed atrophic maxillary posterior ridges in 26 patients with an RBH of only 3–5 mm using a two-stage, transalveolar sinus lift technique. Krasny et al combined the benefits of low risk of complications of a transalveolar sinus lift with an extended augmentation of a lateral window sinus lift.…”
Section: Introductionmentioning
confidence: 99%
“…Direct sinus augmentation in either one stage or two stage can be performed when bone height was less than 6 mm and indirect sinus augmentation when bone height was 6-8 mm [15].In this study patients with bone height 5 mm or less were opted for direct sinus augmentation and patients with bone height of > 5 mm were opted for indirect sinus augmentation which is consistent with the patient selection criteria of studies conducted by S.M Balaji 11 , Ramanuj C Tandel et al [7].The ideal healing time when prosthesis can be constructed as described by Misch 8 -1) SA1 when bone height is 12 mm or more, 4-8 months before abutment placement, 2) SA 2 when bone height is 8-12 mm, 6-8 months before abutment placement, 3) SA 3 when bone height is 5-8 mm, 6-10 months before implant placement, 4) SA 4 when bone height is <5 mm, healing period is 4-10 months after 1 st surgery followed by another 4-10 months after 2 nd surgery. This presents a major drawback as it adds an undesirable longer waiting period for the patient to get permanent prosthesis after a standard sinus lift [1]Study by Cannizzaro et al [16]revealed that it is possible to load implants as early as 7 weeks when placed with initial torque of 35 Ncm in 4-4.5 mm of mean residual bone height below the maxillary sinus. This observation arises question whether sinus lift procedure adds any additional benefit to implant success as graft cannot be transformed in supporting bone in less than 2 months.…”
Section: Asian Pacific Journal Of Health Sciences 2017; 4(1):201-216mentioning
confidence: 99%
“…Bone atrophy in the maxilla is a physiological process, which gets accelerated in case of tooth extraction [1].In post-extraction phase initially there is decrease in bone width due to the resorption of the buccal bone plate causing a continuing loss of bone height and density and an increase in antral pneumatization because of the increased osteoclastic activity of the periostium of the Schneiderian membrane, furthermore increase in positive intra antral pressure [2].Anatomical limitations associated with implant placement in the posterior maxilla are flat palatal vault, deficient alveolar height, inadequate posterior alveolus, increased ______________________________ *Correspondence Debiprasad Ghatak MDS oral & maxillofacial surgery, Dipti general nursing home, 227 Barakar Road, Raghunathpur, Purulia, West Bengal 723133, India E Mail: ghatak2105@gmail.com pneumatization of maxillary sinus causing close approximation of sinus to crestal bone which limit implant placement in these conditions [3]The sinus augmentation technique was first presented in the late 1970s in a series of lectures by Tatum and first published by Boyne and James in 1980 [4][5][6]Sinus elevation using this lateral window approach require extensive surgical manipulation and prolonged waiting period. To overcome the disadvantages of lateral window method and to augment the bone for implant placement in a simpler less invasive manner Summer's 1994 proposed the osteotome technique or the indirect sinus lifting.…”
Section: Introductionmentioning
confidence: 99%
“…Maxillary sinus floor elevation techniques have been applied in the clinics for such cases for decades to augment the insufficient alveolar bone via elevating the maxillary sinus floor [3,4]. The success rate of dental implantation for such cases is still unsatisfactory [5], although significant progress has been made in the area of dental implantation by developing new techniques, implants, bone grafting materials and novel tools [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%